WILLIAM NASSAU SENIOR AND THE RELATIONSHIP BETWEEN ABSTINENCE, CAPITAL AND INTEREST - MORSELLI, Alessandro (Theoretical and Practical Research in Economic Fields, 2019)
This paper highlights Senior’s credit for having introduced the analysis of “abstinence” into the economic vocabulary and its importance in the formation of capital; and also, how the latter, with him, undergoes a strong improvement compared to the original formulations. It is reasonable to believe that Senior’s influence was truly important, since all the subsequent efforts to extend the analysis of marginal utility to the distribution of resources over time by the concept of temporal rate derive from Senior’s theory of abstinence.